Peningkatan Hasil Belajar Materi Keragaman Sosial dan Budaya Indonesia Menggunakan Pembelajaran Kooperatif Tipe SAL - Mukhtar Mukhtar (CV. Syntax Corporation Indonesia, 2023)
The purpose of this study is to Improve Learning Outcomes of Indonesian Social and Cultural Diversity Material Using SAL Type Cooperative Learning for Class VII Students of UPT SMP Negeri 4 Enrekang. The method used in this study is Action Research which consists of 2 (two) cycles, and each cycle consists of: Planning, Implementation, Observation, and Reflection. Based on the results of action research that SAL Type Cooperative Learning can Improve Learning Outcomes of Indonesian Social and Cultural Diversity Material for Class VII Students of UPT SMP Negeri 4 Enrekang. Furthermore, the researchers recommend: (1) For teachers who have the same difficulties can apply SAL Type Cooperative Learning to improve Learning Outcomes. (2) In order to get maximum results, teachers are expected to make SAL Type Cooperative Learning more interesting and varied